Cancer incidence in indigenous people in Australia, New Zealand, Canada, and the USA: a comparative population-based study. Issue 15 (November 2015) - Moore, Suzanne P; Antoni, Sébastien; Colquhoun, Amy; Healy, Bonnie; Ellison-Loschmann, Lis; Potter, John D; Garvey, Gail; Bray, Freddie
Summary: Introduction: Indigenous people have disproportionally worse health and lower life expectancy than their non-indigenous counterparts in high-income countries. Cancer data for indigenous people are scarce and incidence has not previously been collectively reported in Australia, New Zealand, Canada, and the USA. We aimed to investigate and compare, for the first time, the cancer burden in indigenous populations in these countries. Methods: We derived incidence data from population-based cancer registries in three states of Australia (Queensland, Western Australia, and the Northern Territory), New Zealand, the province of Alberta in Canada, and the Contract Health Service Delivery Areas of the USA. Summary rates for First Nations and Inuit in Alberta, Canada, were provided directly by Alberta Health Services. We compared age-standardised rates by registry, sex, cancer site, and ethnicity for all incident cancer cases, excluding non-melanoma skin cancers, diagnosed between 2002 and 2006. Standardised rate ratios (SRRs) and 95% CIs were computed to compare the indigenous and non-indigenous populations of each jurisdiction, except for the Alaska Native population, which was compared with the white population from the USA. Findings: We included 24 815 cases of cancer in indigenous people and 5 685 264 in non-indigenous people from all jurisdictions, not including Alberta, Canada. The overall cancer burden in indigenous populations was substantially lower in the USA except in Alaska, similar or slightly lower in Australia and Canada, and higher in New Zealand compared with their non-indigenous counterparts. Among the most commonly occurring cancers in indigenous men were lung, prostate, and colorectal cancer. In most jurisdictions, breast cancer was the most common cancer in women followed by lung and colorectal cancer. The incidence of lung cancer was higher in indigenous men in all Australian regions, in Alberta, and in US Alaska Natives than in their non-indigenous counterparts. For breast cancer, rates in women were lower in all indigenous populations except in New Zealand (SRR 1·23, CI 95% 1·16–1·32) and Alaska (1·14, 1·01–1·30). Incidence of cervical cancer was higher in indigenous women than in non-indigenous women in most jurisdictions, although the difference was not always statistically significant. Interpretation: There are clear differences in the scale and profile of cancer in indigenous and non-indigenous populations in Australia, New Zealand, Canada, and the USA. Our findings highlight the need for much-improved, targeted programmes of screening, vaccination, and smoking cessation, among other prevention strategies. Governments and researchers need to work in partnership with indigenous communities to improve cancer surveillance in all jurisdictions and facilitate access to cancer data. Funding: International Agency for Research on Cancer–Australia Fellowship.